Environmental Sanitation Education in Reducing Environmental Pollution in the Siak River Area - Zulmeliza Rasyid; Novita Rany; Nurvi Susanti; Nila Puspita Sari; Suherman Sohor (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Environmental pollution in the Siak River area is a serious problem impacting public health and the ecosystem. To address this issue, environmental sanitation education activities are being implemented to raise public awareness about the importance of good sanitation practices. Methods include outreach and hands-on practice in waste management. Health education is being conducted in the Meranti Pandak Village area. The media used for the education are laptops, n-focus, and leaflets. The methods used in the education are lectures and question-and-answer discussions. This community service activity will be conducted in July 2025. The results of this activity indicate an increase in public understanding of the importance of sanitation and waste management. There was increased knowledge 48% in knowledge, 49% in attitudes, and 48% in actions of respondents before and after the questionnaire was administered. The community is beginning to actively participate in maintaining the cleanliness of their environment. Sanitation education plays a crucial role in reducing pollution and improving environmental quality. It is hoped that it can be implemented sustainably to create a cleaner and healthier environment.